Comparison of operative procedures for re-leaks duodenal perforation: a cross-sectional analysis from a tertiary care hospital in a developing country - Sanjanwala, Saurabh S.; Thati, Vinaykumar N.; Rohondia, Omprakash S.; Rambhia, Samir U. (International Surgery Journal, 2016)
Background:Re-leaks following surgical closure of duodenal perforations is a well known entity. Considering the paucity of data on patients with re-leak from Indian population, the present study was carried out. Methods: The present study is a prospective audit of patients diagnosed with duodenal re-leak and surgical procedures for arresting the leak was done. Hospital indoor case records were reviewed from 2005 to 2010. Following details were collected: demographic details (age and sex); presenting complaints; success of the surgical procedures to arrest re-leak and overall survival of patients. Conservative measures, 3 tubes method, jejunal patch, T tube duodenostomy and rohondia’s cholecystoduodenoplasty were the type of procedures routinely performed for such patients. Descriptive statistics was used to represent various variables-mean (SD) for continuous and proportions (percentages) for categorical variables. Results:A total of 41 patients with duodenal re-leak requiring intervention were identified with mean (range) of age in years of 45 (25-65).The following types of procedures were carried out to arrest duodenal re-leaks: 3 tubes method (4/41, 9.8%), jejunal patch (7/41, 17.1%), T tube duodenostomy (1/41, 2.4%) and Rohondia’s cholecystoduodenoplasty (16/41, 39%) and conservative (13/41, 31.7%). A total of 75% (12/16) success in stopping the leak was observed with Rohondia’s cholecystoduodenoplasty followed by 1/4 (25%) with 3 tubes duodenostomy, one each with jejunal patch (14.3%) and conservative techniques (7.7%) and none with T- tube duodenostomy (P-0.1; not significant). A total of 32/41 (78%) patients died following the surgery for duodenal re-leak of which nearly four-fifths of them (26/32, 81%) died due to septicaemia, 5/33 (15.2%) had pulmonary complications and 1/33 (3%) due to perforation. Conclusions:To conclude, the present study gives baseline data on patients who have undergone various surgical procedures for arresting duodenal perforation but had re-leaks, in a tertiary care hospital of a developing country. The better outcomes associated with Rohondia’s cholecystoduodenoplasty was found in comparison to other surgical and conservative measures.